The use of circular frame external fixation in the treatment of ankle/hindfoot Charcot Neuroarthropathy - Martin, Brian (J Clin Orthop Trauma, 2021)
Charcot Neuroarthropathy (CN) of the ankle/hindfoot is a devastating condition that results in a loss of alignment, bony malleolar protrusions and frequently leads to ulceration, infection, and amputation. Major limb amputations in this patient population has a 5-year mortality rate approximating 39%–68%. The treatment goal for CN of the ankle/hindfoot is to provide stability with a plantigrade foot that is infection free, shoeable and allows independent weight bearing. The use of a circular frame external fixator is often required when treating patients with CN of the ankle/hindfoot because they often present late with deformity, soft tissue compromise and infection which are contraindications to primary internal fixation. These patients require urgent surgical attention to salvage the limb or risk amputation. In this narrative review article we will discuss the indications, management options, surgical technique, evidence and describe our experience in the use of circular frame external fixation in patients with ankle/hindfoot Charcot Neuroarthropathy.